The Carotid Endarterectomy Cadaveric Investigation for Cranial Nerve Injuries: Anatomical Study - Cevik, Orhun Mete; Usseli, Murat Imre; Babur, Mert; Unal, Cansu; Eksi, Murat Sakir; Guduk, Mustafa; Ovalioglu, Talat Cem; Aksoy, Mehmet Emin; Pamir, M. Necmettin; Bozkurt, Baran (MDPI, 2021)
Cerebral stroke continues to be one of the leading causes of mortality and long-term morbidity

therefore, carotid endarterectomy (CEA) remains to be a popular treatment for both symptomatic and asymptomatic patients with carotid stenosis. Cranial nerve injuries remain one of the major contributor to the postoperative morbidities. Anatomical dissections were carried out on 44 sides of 22 cadaveric heads following the classical CEA procedure to investigate the variations of the local anatomy as a contributing factor to cranial nerve injuries. Concurrence of two variations was found to be important in hypoglossal nerve injury: the presence of a direct smaller vein in proximity of the carotid bifurcation, and the intersection of the hypoglossal nerve (HN) with this vein. Based on the sample investigated, this variation was observed significantly higher on the right side. Awareness of possible anatomical variations and early ligation of any small veins can significantly decrease iatrogenic injury risk.
Keywords: carotid endarterectomy; cadaveric study; local venous anatomy; carotid endarterectomy postoperative morbidities; cranial nerve injuries